1995
DOI: 10.1002/chin.199506020
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Alumina‐Supported Manganese Oxide Catalysts. Part 1. Characterization: Effect of Precursor and Loading.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 1 publication
3
41
0
1
Order By: Relevance
“…XPS measurements were carried out to confirm the presence of Mn and its oxidation state. Figure 5(b) shows the Mn 2p photoelectron peak of Mn-TiO 2 : the binding energy of Mn 2p 3/2 at 641.8 eV can be ascribed to Mn 3+ , while the other peak at 642.4 eV originates from Mn 4+ [19][20][21][22][23]. The presence of Mn 4+ has a certain influence on the XPS spectrum of Ti 2p (Fig.…”
Section: Inhibition Effect Of Mn 2+ On the Crystallization Of Tiomentioning
confidence: 95%
“…XPS measurements were carried out to confirm the presence of Mn and its oxidation state. Figure 5(b) shows the Mn 2p photoelectron peak of Mn-TiO 2 : the binding energy of Mn 2p 3/2 at 641.8 eV can be ascribed to Mn 3+ , while the other peak at 642.4 eV originates from Mn 4+ [19][20][21][22][23]. The presence of Mn 4+ has a certain influence on the XPS spectrum of Ti 2p (Fig.…”
Section: Inhibition Effect Of Mn 2+ On the Crystallization Of Tiomentioning
confidence: 95%
“…Both the oxides possess strong basic sites that may interact with the manganese ions contained in the acidic solution of the nitrate precursor during the preparation. During the calcination, residues of the manganese salts and solvating water are removed and some condensation, resulting in bond formation between the support surface oxygen and manganese may occur [23]. This may indicate that the surface lattice oxygen is then less susceptible for the interaction with H2S and it may rather be the bulk lattice oxygen that participates in the sorption process.…”
Section: Mno-support + H2s ↔ Mns-support + H2omentioning
confidence: 99%
“…The new diffraction lines observed after the impregnation are attributed to Mn2O3. The presence of this oxide can be expected when considering the manganese precursor used, Mn loading and calcination temperature [11,23,29,30]. These factors have a strong influence on the properties of the manganese species formed during the preparation.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Kapteijn et al, (1994aKapteijn et al, ( , 1994b found that a Mn/ Al 2 O 3 catalyst obtained from manganese acetate had better activity than a catalyst produced from manganese nitrate. This was attributed to highly dispersed manganese oxides on the catalyst surface.…”
Section: Introductionmentioning
confidence: 99%